2002
DOI: 10.1094/phyto.2002.92.5.527
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Chlorosis-Inducing Toxin from Pyrenophora tritici-repentis and the Chromosomal Location of an Insensitivity Locus in Wheat

Abstract: Culture filtrate from Pyrenophora tritici-repentis race 1 isolate 78-62 contained a genotype-specific toxin which elicited extensive chlorosis on sensitive wheat genotypes. This toxin was partially purified using gel filtration, ion exchange, and reversed-phase chromatography. The chlorosis toxin was found to be a polar, nonionic, low-molecular-weight molecule. Wheat genotypes infiltrated with crude culture filtrate and partially purified chlorosis toxin exhibited the same chlorotic symptoms seen with conidial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
170
0
12

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(190 citation statements)
references
References 29 publications
8
170
0
12
Order By: Relevance
“…P. tritici-repentis produces various HSTs, each of which uniquely leads to progression of disease on wheat cultivars that are sensitive to that particular toxin (reviewed in De Wolf et al, 1998;Ciuffetti and Tuori, 1999;Strelkov and Lamari, 2003). Of the three HSTs thus far characterized from P. tritici-repentis, two-Ptr ToxA (Ballance et al, 1989;Tomas et al, 1990;Tuori et al, 1995;Zhang et al, 1997) and Ptr ToxB (Strelkov et al, 1998)-have been shown to be proteins, whereas Ptr ToxC is a low molecular weight compound (Effertz et al, 2002). For Ptr ToxA (hereafter called ToxA), the first protein HST to be isolated (Ballance et al, 1989;Tomas et al, 1990;Tuori et al, 1995;Zhang et al, 1997), sensitivity is conditioned by the presence of a single host locus, Tsn1, on the 5BL chromosome (Faris et al, 1996;Stock et al, 1996;Gamba et al, 1998;Anderson et al, 1999) and the ToxA gene in the fungus (Ballance et al, 1996;Ciuffetti et al, 1997); disease occurs only when both the genes are present.…”
Section: Introductionmentioning
confidence: 99%
“…P. tritici-repentis produces various HSTs, each of which uniquely leads to progression of disease on wheat cultivars that are sensitive to that particular toxin (reviewed in De Wolf et al, 1998;Ciuffetti and Tuori, 1999;Strelkov and Lamari, 2003). Of the three HSTs thus far characterized from P. tritici-repentis, two-Ptr ToxA (Ballance et al, 1989;Tomas et al, 1990;Tuori et al, 1995;Zhang et al, 1997) and Ptr ToxB (Strelkov et al, 1998)-have been shown to be proteins, whereas Ptr ToxC is a low molecular weight compound (Effertz et al, 2002). For Ptr ToxA (hereafter called ToxA), the first protein HST to be isolated (Ballance et al, 1989;Tomas et al, 1990;Tuori et al, 1995;Zhang et al, 1997), sensitivity is conditioned by the presence of a single host locus, Tsn1, on the 5BL chromosome (Faris et al, 1996;Stock et al, 1996;Gamba et al, 1998;Anderson et al, 1999) and the ToxA gene in the fungus (Ballance et al, 1996;Ciuffetti et al, 1997); disease occurs only when both the genes are present.…”
Section: Introductionmentioning
confidence: 99%
“…1AS, 1BS, 6BS, 4AL, 6AL, 2BL, 3BL, 5BL, and 7BL. Of these genomic regions previous studies had identified that 1AS and 5BL harbor major genes for resistance to tan spot caused by toxins Ptr ToxC and Ptr ToxA, respectively (Anderson et al 1999;Effertz et al 2002). Additionally studies had identified race-specific and race non-specific QTLs on chromosomes 1BS, 6BS, 4AL, 2BL, and 3BL (Faris & Friesen 2005;Singh et al 2008b).…”
Section: Resultsmentioning
confidence: 99%
“…Major genes for resistance to tan spot have been reported on chromosomes 1AS, 3A, 2BS, 3BL, 5BL, and 3DS (Lamari & Bernier 1989b;Anderson et al 1999;Effertz et al 2002;Singh et al 2006aSingh et al , 2008aTadesse et al 2007;Singh et al 2010). Additional quantitative trait loci (QTLs) have been located on chromosomes 2AS, 3AS, 4AL, 5AL, 1BS, 2BL, 3BS, 3BL, 2DS, 2DL, and 7DS (Faris et al 1997;Friesen & Faris 2004;Faris & Friesen 2005;Chu et al 2008;Singh et al 2008b;Singh et al 2010).…”
Section: S103mentioning
confidence: 99%
“…Effertz et al, (2002), proved its production in culture from the isolate of race 1 and it was partially purified. The production of this toxin by isolates classified as races 3, 6 and 8 was proved by several researches (Gamba et al, 1998;Lamari & Bernier, 1991;Lamari et al, 2003;Strelkov et al, 2002;).…”
Section: The Host Selective Toxin Produced By Pyrenophora Tritici-repmentioning
confidence: 98%
“…The HSTs are responsible for disease symptoms on susceptible wheat cultivars and lines. At the present, three toxins have been described (Ballance et al, 1989;Ciuffetti et al, 1998;Effertz et al 2002;Martinez et al 2001;Tomas et al, 1990;Touri et al, 1995;Strelkov et al 1999Strelkov et al , 2006. It is commonly accepted that the names of toxin are Ptr Tox A, Ptr Tox B and Ptr Tox C (Ciuffetti et al 1998).…”
Section: The Host Selective Toxin Produced By Pyrenophora Tritici-repmentioning
confidence: 99%